The human electrocerebellogram (ECeG) recorded non-invasively using scalp electrodes. (24th August 2018) - Todd, Neil P.M.; Govender, Sendhil; Colebatch, James G.
Highlights: High-frequency signals characteristic of the electrocerebellogram (ECeG) have been recorded from over the human posterior fossa. These high-frequency signals are unlikely to be generated in either the adjacent occipital cortex or the muscles of the neck. The signals also show strong modulation by visual motion, consistent with the known behaviour of cerebellar cortex. The human ECeG may allow better understanding of cerebellar function and may also have potential as a clinical tool. Abstract: The electrocerebellogram (ECeG), a manifestation of cerebellar cortical local field potentials (LFPs), is characterised by a predominance of high frequency components at the gamma range (30–80 Hz) and beyond up to several hundred Hz, in contrast to the electroencephalogram (EEG) which is composed predominantly of lower frequencies at or below the gamma range. Although the potential clinical role of the ECeG has been suggested, the prospect of a non-invasive method for routine recording in humans has remained elusive. Here we show for the first time that high-frequency power characteristic of the ECeG may be easily measurable using surface electrodes placed over the posterior fossa at the approximate original 10/20 CB location. In a sample of six subjects we have compared continuous electrical recordings in a supine posture under visual motion stimulation at CB1/2, about 5% inferior and medial to PO9/10 of the 10–10 system, with those at standard 10/20 locations of C3/4 and O1/2, as well as over the splenius muscles as controls against myogenic contamination. In a neutral baseline condition high-frequency power was significantly greater over the posterior fossa, especially in ultra-gamma (80–160 Hz) and very high frequency (VHF, 160–320 Hz) bands, compared to occipital or central leads. We also found that visual stimulation, in the form of visual motion in particular, was effective in increasing the high-frequency power in CB electrodes, including in beta (14–30 Hz) and gamma, compared with electrodes over the occipital and frontal cortex. We propose that the human ECeG can be recorded non-invasively and may have application both in understanding cerebellar function and clinically.